Factibilidad financiera y social para un comedor Comunitario en el barrio coronado de Palmira Valle (2023)
The present study and research focuses on carrying out a financial feasibility study verifying the social impact of the community for the implementation of a community kitchen in the Coronado de Palmira neighborhood located in the department of Valle in Colombia.